Nicotine Changes the microRNA Profile to Regulate the FOXO Memory Program of CD8+ T Cells in Rheumatoid Arthritis - Wasén, Caroline; Ospelt, Caroline; Camponeschi, Alessandro; Erlandsson, Malin C.; Andersson, Karin M. E.; Silfverswärd, Sofia Töyrä; Gay, Steffen; Bokarewa, Maria I. (Frontiers in Immunology, 2020)
OBJECTIVE. Smoking suppresses PD-1 expression in patients with rheumatoid arthritis (RA). In this study, we assess if smoking changed the epigenetic control over CD8+ T cell memory formation through a microRNA (miR) dependent mechanism. METHODS. Phenotypes of CD8+ T cells from smokers and non-smokers, RA and healthy, were analyzed by flow cytometry. A microarray analysis was used to screen for differences in miR expression. Sorted CD8+ cells were in vitro stimulated with nicotine and analyzed for transcription of miRs and genes related to memory programming by qPCR. RESULTS. CD27+CD107a–CD8+ T cells, defining a naïve-memory population, had low expression of PD-1. Additionally, the CD27+ population was more frequent in smokers (p=0.0089). Smokers were recognized by differential expression of 8 miRs. Let-7c-5p, let-7d-5p and let-7e-5p, miR-92a-3p, miR-150-5p and miR-181-5p were up regulated, while miR-3196 and miR-4723-5p were down regulated. These miRs were predicted to target proteins within the FOXO-signaling pathway involved in CD8+ memory programming. Furthermore, miR-92a-3p was differentially expressed in CD8+ cells with naïve-memory predominance. Nicotine exposure of CD8+ cells induced the expression of miR-150-5p and miR-181a-5p in the naïve-memory cells in vitro. Additionally, nicotine exposure inverted the ratio between mRNAs of proteins in the FOXO pathway and their targeting miRs. CONCLUSIONS. Smokers have a high prevalence of CD8+ T cells with a naïve-memory phenotype. These cells express a miR profile that interacts with the memory programming conducted through the FOXO pathway.